Variations of root and canal morphology of mandibular second molars in Chinese individuals: a cone-beam computed tomography study - Lin Yang; Jingchao Han; Qibao Wang; Zhuoran Wang; Xijiao Yu; Yi Du (BMC, 2022)
Abstract Background The mandibular second molars demonstrate variations on root and canal morphology. The aim of this study was to investigate all the root canal morphology of mandibular second molars and analyze the morphological variations in patients by gender and age in a Chinese population use CBCT imaging. Methods Cone-beam computed tomographic images of 1200 bilateral mandibular second molars were obtained from 600 patients (300 females and 300 males) who required a preoperative assessment for implant surgery, surgical removal of impacted teeth, orthodontic treatment, surgery of maxillofacial tumour and cysts or LeFort I osteotomy. CBCT images were divided into 5 groups according to age: "15-24 years", "25-34 years", "35-44 years", "45-54 years" and "≥ 55 years"; and 2 groups by gender: "females" and "males". The following information were recorded: the number of roots and canals and their morphology, the frequency and configuration of C-shaped canals by gender, age and position (left and right). The chi-square test was used to analyse differences between groups. P value of < 0.05 was considered statistically significant. Results Of the 1200 teeth, 61% had two separate roots located mesiodistally, 35.6% had one C-shaped root. The 45.3% teeth had three canals in two-rooted mandibular second molars. The mesial root showed a Vertucci type II configuration in 28.9% cases followed by type IV(24.4%). While the distal root showed a significant higher prevalence of type I configuration in 95.6%. In the examined 1200 teeth, 430 teeth (35.8%) had C-shaped root canals. The prevalence of C-shaped root canal systems was significantly higher in females (42.5%) than in males (29.1%) (P = 0.000), and did not differ with age (P = 0.126). The 80.4% C-shaped canals were bilateral (P = 0.000) and did not differ with side (left and right) (P = 0.758). Conclusions The most commonly observed root morphology for the mandibular second molars was 2 separate roots with three canals.The prevalence of C-shaped root canal is 35.8% and is more higher in females than in males.